Pengaruh PENGARUH MOTIVASI, KOMUNIKASI DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK X - Suprianto, Jeki Suprianto; Vanomy, Afrianti Elsye (Fortunate Business Review, 2023)
The purpose of this research is to determine the effect of motivation on job satisfaction, the effect of communication on job satisfaction, and the effect of work stress on job satisfaction in PT employees. Bank X in Batam City partially or simultaneously. This research uses a quantitative research approach, the data used is primary data obtained through distributing questionnaires to 82 employees of PT. Bank X in Batam City. Partial Least Square – Structural Equation Modeling (PLS-SEM) with WarpPLS version 7.0 was used for data analysis. The research results concluded that the first hypothesis test showed that motivation had a significant effect on job satisfaction, communication had no significant effect on job satisfaction, and work stress had a significant effect on job satisfaction. Meanwhile, motivation, communication and work stress do not have a significant effect on job satisfaction for PT Bank X employees in Batam City.